2015
DOI: 10.4314/just.v34i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of shea nut (<i>Vitellaria paradoxa</i>, gaertn) byproducts and their digestibility by Nile tilapia (<i>Oreochromis niloticus</i> L.) juvenile

Abstract: This study was conducted to determine the nutritional (proximate and energy) composition of selected shea nut by-products (SNPs) namely; shea nut meal (SNM, solvent extracted), shea nut cake (SNC, mechanically extracted) and shea nut cake (SNCW, water extracted) and their apparent digestibility coefficient (ADC) by Nile tilapia, Oreochromis niloticus. The ADC was determined using a reference diet with chromic oxide indicator and test diets that contained 70% reference diet and 30% of SNPs being evaluated. Nile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…The least content of ash (2.65+0.02%) was found in Vitellaria paradoxa fruits. This is contrary to submission by Agbo, et al [23]; Akoma, et al [20] who reported high ash content in Vitellaria paradoxa fruits. But the result agrees with Adebayo and Ojo [21] who stated low ash content in Afzelia africana seeds.…”
Section: Discussioncontrasting
confidence: 98%
“…The least content of ash (2.65+0.02%) was found in Vitellaria paradoxa fruits. This is contrary to submission by Agbo, et al [23]; Akoma, et al [20] who reported high ash content in Vitellaria paradoxa fruits. But the result agrees with Adebayo and Ojo [21] who stated low ash content in Afzelia africana seeds.…”
Section: Discussioncontrasting
confidence: 98%
“…Previous studies on oilseed meal-based diets fed to various animals have reported negative, although highly variable, effects on production performance. For instance, studies where shea nut meal based diets were fed to broiler chickens ( Atuahene et al., 1998 ) and Nile tilapia ( Agbo et al., 2014 ), observed low growth performance caused by poor digestibility, and possibly reduced feed intake ( Elemo et al., 2011 ). Dabrowski and Kozak (1979) observed a lower growth performance in grass carp fry fed with different levels of commercial soybean meal compared to fishmeal.…”
Section: Introductionmentioning
confidence: 99%